Hermeneutika Lintas Tekstual: Alternatif Pembacaan Alkitab Dalam Merekonstruksi Misiologi Gereja Suku di Indonesia - Pelita Hati Surbakti; Noel GBP Surbakti (Reformed Center for Religion and Society, 2019)
On November 7, 2017, the Constitutional Court of the Republic of Indonesia, decision number 97/PUU-XIV/2016, finally granted an accusation against several points of the Demography Administration Law. If not properly addressed, the decision will erode the number of members of the ethnic churches in Indonesia. The decision will be a driving force for them to reformulate their identities as believers and not Christians. Two historical backgrounds that made excesses of the decision namely the excesses of the G30S/PKI 1965 events that caused a large number of local believers to become Christians and the European nation's missionary legacy that was less friendly to Indonesian local cultures. To address this, I propose an alternative reading of the Bible that is friendlier to local beliefs - namely Cross-textual Hermeneutics. I will use the Protestant Batak Karo Church (GBKP) as a case study.Â Keywords: Hermeneutics, mission, identity, Karo, cultural-belief, Cross-textual Hermeneutics.